2021
DOI: 10.24875/ric.20000010
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Associated Motor and Non-motor Factors in People with Parkinson's Disease

Abstract: Background: People with Parkinson's disease (PwP) are at higher risk of developing malnutrition. Several factors have been suggested to be involved including motor symptoms, non-motor symptoms, and treatment-related complications. Objective: The objective of the study was to analyze the combined effect of motor, non-motor, and pharmacological factors in the risk of malnutrition in PwP. Methods: Eighty-seven consecutive PwP were included in the study. Clinical data and pharmacological treatment were collected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the rate of WL in the present study (− 1.54% [IQR, − 3.32-1.06]) was lower in comparison to previous studies (3-5%) [19], and stable BMI (25.1 kg/m2 [IQR, 19.2-25.0]), may be in uenced by the fact that study population was in better condition in comparison to patients who were placed under the control of expert neurologists. PD patients are reported to be at risk of malnutrition [20][21][22][23][24]. However, in this study, most participants who received DBS and LCIG therapies were regularly admitted to our hospital for scheduled neurological examinations after surgery and could be well-managed in a state of normal nutrition or mild malnutrition.…”
Section: Discussionmentioning
confidence: 87%
“…However, the rate of WL in the present study (− 1.54% [IQR, − 3.32-1.06]) was lower in comparison to previous studies (3-5%) [19], and stable BMI (25.1 kg/m2 [IQR, 19.2-25.0]), may be in uenced by the fact that study population was in better condition in comparison to patients who were placed under the control of expert neurologists. PD patients are reported to be at risk of malnutrition [20][21][22][23][24]. However, in this study, most participants who received DBS and LCIG therapies were regularly admitted to our hospital for scheduled neurological examinations after surgery and could be well-managed in a state of normal nutrition or mild malnutrition.…”
Section: Discussionmentioning
confidence: 87%
“…Mini Nutritional Assessment is used for assessing the nutritional status of patients. There were 22 studies included in which MNA assessments were conducted [ 10 , 11 , 12 , 16 , 17 , 18 , 19 , 21 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. There was a total of 2713 participants, of which 39.2% were female and 60.8% were male.…”
Section: Resultsmentioning
confidence: 99%
“…We took into consideration 49 studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] in which BMI was assessed, resulting in 5727 patients, 57.3% of whom were men and 40.9% of whom were women. The lowest reported mean BMI was 17.84 kg/m 2 [ ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a three-year cohort study found a direct relationship between constipation and body fat loss [ 39 ]. Additionally, researchers observed a direct relationship between an individual’s risk of malnutrition and motor symptom severity [ 40 , 41 ]. Other nutrition-related symptoms may include dementia, depression, dyskinesia, dysphagia, gastroparesis, hyposmia, tremors, rigidity, and small bowel dysfunction [ 38 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%